Clinical Biomechanics and Related Research - Hirasawa, Yasusuke; Sledge, Clement Blount; Woo, Savio Lau-Yuen (Springer Japan, 1994)
Clinical biomechanics is a rapidly changing field with an increasingly wide appeal. While the core subjects of biomechanics remain the behavior of bones, joints, ligaments, and muscles, this book focuses on more clinical aspects such as artificial joints, tissue transplantations, and the effects of disease on biomechanical properties. Also featured are special studies of the hand, spine, vascular system, and the analysis of three-dimensional motion. Based on the 20th Annual Meeting of the Japanese Society for Clinical Biomechanics and Related Research, this book provides an overview of the subject as well as describing many exciting new concepts and innovative methods for analyzing biomechanical systems. It should appeal across a wide spectrum of professions, proving indispensable to everyone from orthopedic surgeons to engineers with an interest in biology